2018
DOI: 10.1177/1010539517751349
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Indicators of Suicide in Cambodian Women

Abstract: Global suicide rates are steadily increasing, and suicide completions in Asia outnumber those in Western countries. Young females are especially at risk, with higher rates of completion and lack of suicide support because of familial and cultural stigma and constraints. Lack of infrastructure to systematically record suicide deaths and attempts makes studying suicide in low- and middle-income countries challenging. Given the critical public health need for suicide intervention and prevention, research on suici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Rates of mental health disorders in Cambodia are higher than in other low-to medium-income countries, with previous findings from the current study indicating elevated national rates of psychopathology, including anxiety (27.4%), depression (16.7%), and PTSD (7.6%) (Seponski et al, 2019). Cambodian women who are younger, single, and uneducated are at even greatest risk for mental illness (Saxena et al, 2007), and previous findings of this study indicated that Cambodian women experiencing depression and PTSD, as well as cultural symptoms or syndromes, are at heightened risk for attempting suicide (Armes et al, 2018). Socioeconomic status (SES) affects mental health among the Cambodian population, with individuals in financial debt experiencing significantly higher rates of anxiety, depression, and PTSD (Seponski et al, 2019).…”
Section: Cambodian Mental Healthsupporting
confidence: 84%
“…Rates of mental health disorders in Cambodia are higher than in other low-to medium-income countries, with previous findings from the current study indicating elevated national rates of psychopathology, including anxiety (27.4%), depression (16.7%), and PTSD (7.6%) (Seponski et al, 2019). Cambodian women who are younger, single, and uneducated are at even greatest risk for mental illness (Saxena et al, 2007), and previous findings of this study indicated that Cambodian women experiencing depression and PTSD, as well as cultural symptoms or syndromes, are at heightened risk for attempting suicide (Armes et al, 2018). Socioeconomic status (SES) affects mental health among the Cambodian population, with individuals in financial debt experiencing significantly higher rates of anxiety, depression, and PTSD (Seponski et al, 2019).…”
Section: Cambodian Mental Healthsupporting
confidence: 84%
“…For example, it is clinically important to know that a Cambodian patient is having orthostatic dizziness, sleep paralysis, or khyaˆl attacks, which produce catastrophic cognitions and great distress. We have shown how these idioms of distress improve over the course of treatment (Hinton, Kredlow, et al, 2012); are a key part of psychopathology such as trauma-related disorder (Hinton et al, 2013;Hinton, Hinton, & Eng, 2015); are at the center of causal networks (Hinton & Good, 2016); are an important indicator of suicide risk (Armes et al, 2018); are a better indicator than PTSD of trauma-event severity and of self-perceived health ; and are important to address in cognitive behaviour therapy (CBT) to modify catastrophic cognitions and to increase credibility and positive expectancy .…”
mentioning
confidence: 99%
“…Some studies mentioned that the younger the age of suicide attempt, the higher the number of repetitions (29). On the other hand, adolescence is a sensitive period in life, and the suicide attempt is increasing among adolescences worldwide, as 8% of high school students stated they experienced at least one suicide attempt (31). The transition from adolescence to adulthood is a vi- tal period so that youth experience many changes in their life goals, emotional bonds, and worldview, which make them more sensitive (32).…”
Section: Discussionmentioning
confidence: 99%